Illustrated key to the species included in the genus Petalops Amyot & Serville, 1843 (Hemiptera: Heteroptera: Coreidae: Coreinae: Acanthocephalini), with description of four new species and new distributional notes - Brailovsky, Harry (Zootaxa, 2021)
Four new species of Petalops Amyot & Serville, 1843 are described: P. graziae from Brazil, P. jactatus from Ecuador, P. lautus from Colombia, and P. necopinus from Peru. A revised key to all known species (16) is included. New distributional data are given for P. ambiguous Brailovsky, 1991, P. bellator Brailovsky, 1991, P. luteomaculosus Brailovsky, 1991, P. occulta Brailovsky, 1991, and P. thoracicus (Thunberg), 1783. Dorsal view photos are added of all the known species.